Collaboration between professionals and mothers to enhance oral communication competence in bilingual children with language disorders in inclusive contexts - Gonzalez, Diana Patricia; Gràcia, Marta; Adam-Alcocer, Ana Luisa (Frontiers in Education, 2025)
IntroductionResearch on the effectiveness of family interventions is essential for enhancing the oral communicative competence of children with developmental language disorders. This study examined mother–child interactions in bilingual Spanish–English families to identify current communication strategies and explore additional ways to foster oral communicative competence development.MethodsParticipants included 10 mothers and their bilingual children (ages 4–6 years) with language disorders, along with a school-based speech-language pathologist from a public school in New York. The Scale for the Assessment of Oral Language Teaching in Family Contexts was used to evaluate mother–child interactions. A collaborative intervention consisting of four school-based workshops was implemented to foster mothers’ awareness of their communicative practices and support them in strengthening their interactions with their children.ResultsDuring the workshops, mothers engaged in discussions with the school-based speech-language pathologist, reflecting on and refining their communication strategies. By the end of the intervention, some mother–child dyads showed noticeable improvements in the quality of their interactions.DiscussionThe mothers’ evaluations highlight their active engagement in the collaborative process and their commitment to improving communication with their children to support oral communicative competence development.